Treatment for cellulite - Neil Sadick, MD (Wolters Kluwer, 2019)
Cellulite is a multifactorial condition that is present in 80% to 90% of postpubertal women and is one of the most intolerable esthetic imperfections. There are several theories on the pathophysiology of cellulite, and a number of different therapeutic regimens have been developed, from topical treatments to mechanical or energy-based devices. In this brief review, we summarize the scientific landscape to determine the clinical evidence with regard to the safety and efficacy of cellulite treatment options. Clinical protocols and the author's experience using a combination of internal and external procedures are also discussed. Studies using laser and light modalities along with radiofrequency have shown improvements in cellulite and a good safety profile, but acoustic wave therapy, subcision, and the 1440-nm Nd:YAG minimally invasive laser have demonstrated the most beneficial results in cellulite reduction. Although there is paucity of scientific evidence for treatments that improve cellulite, future emerging options and their combination may pave the way to eradicate this primarily cosmetic esthetic concern. Keywords: Cellulite, pathophysiology, adipocytes, radiofrequency, lasers